Adubação foliar na qualidade e produtividade de abacaxi - Maeda, Alexandra Sanae; Buzetti, Salatiér [UNESP]; Boliani, Aparecida Conceição [UNESP]; Benett, Cleiton Gredson Sabin; Filho, Marcelo Carvalho Minhoto Teixeira [UNESP]; Andreotti, Marcelo [UNESP] (My University, 2011)
There are just a few studies using foliar sprays with micronutrients on pineapple crops. The objective of this study was to evaluate the B and Zn effect, as chelate, acid or salt, via foliar feeding, on fruit yield and quality. The experiment was carried out in Guaraçaí, São Paulo State, Brazil, in a loamy medium texture soil, by using Smooth Cayenne (Hawaiian) pineapple seedlings. A randomized block design with four replications was adopted, with 110 g ha-1 of B and 250 g ha-1 of Zn for each application. Two foliar sprays were applied, at 7 and 9 months after planting. The B and Zn sources did not affect the total soluble solids contents, titratable acidity, average fruit diameter, fruit length without crown, and maturity index. Only the B, Zn, and K concentrations in the leaves were influenced by the application of micronutrients.
Foliar fertilization on pineapple quality and yield
Keywords: Ananas comosus L.; Boron;zinc; Smooth cayenne